Effect of voluntary ethanol consumption combined with testosterone treatment on cardiovascular function in rats: Influence of exercise training - Engi, Sheila A. [UNESP]; Planeta, Cleopatra S. [UNESP]; Crestani, Carlos C. [UNESP] (Public Library of Science (PLoS), 2016)
This study evaluated the effects of voluntary ethanol consumption combined with testosterone treatment on cardiovascular function in rats. Moreover, we investigated the influence of exercise training on these effects. To this end, male rats were submitted to low-intensity training on a treadmill or kept sedentary while concurrently being treated with ethanol for 6 weeks. For voluntary ethanol intake, rats were given access to two bottles, one containing ethanol and other containing water, three 24-hour sessions per week. In the last two weeks (weeks 5 and 6), animals underwent testosterone treatment concurrently with exercise training and exposure to ethanol. Ethanol consumption was not affected by either testosterone treatment or exercise training. Also, drug treatments did not influence the treadmill performance improvement evoked by training. However, testosterone alone, but not in combination with ethanol, reduced resting heart rate. Moreover, combined treatment with testosterone and ethanol reduced the pressor response to the selective α1-adrenoceptor agonist phenylephrine. Treatment with either testosterone or ethanol alone also affected baroreflex activity and enhanced depressor response to acetylcholine, but these effects were inhibited when drugs were coadministrated. Exercise training restored most cardiovascular effects evoked by drug treatments. Furthermore, both drugs administrated alone increased pressor response to phenylephrine in trained animals. Also, drug treatments inhibited the beneficial effects of training on baroreflex function. In conclusion, the present results suggest a potential interaction between toxic effects of testosterone and ethanol on cardiovascular function. Data also indicate that exercise training is an important factor influencing the effects of these substances.